Investigation of Hybrid Simulation With Model Updating Compared to an Experimental Shake Table Test - Ou, Ge; Yang, Ge; Dyke, Shirley; Wu, Bin (Frontiers in Built Environment, 2020)
In hybrid simulation, response time history measured from experimental substructure can be utilized to identify the model associated with the tested specimen in real time. To improve the modeling accuracy, the updated model parameters can substitute the initial parameters of similar components (as the tested specimen) that reside in the numerical substructure. In this study, a detailed investigation on the fidelity improvement using model updating in hybrid simulation is delivered. This study focused on both local and global assessment of hybrid simulation with model updating (HSMU) by comparing HSMU with conventional simulation and shake table testing. In the local assessment, the updating efficiency with different nonlinear models (one phenomenological model, and one FEM model) are illustrated; in the global assessment, the HSMU response time histories are compared to the shake table testing. Observations and comments on model selection, parameter convergence, and time and frequency domain performance of HSMU are provided.